Effect of proprioceptive training in male soccer players - Francisco Tomás González-Fernández; Andrés Mármol Pérez (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Soccer is one of most popular and practiced sports. Although, we can establish its dynamic character as a determining factor that injuries to occur. Although, the majority of injuries are caused by contacts or impacts, a wide part of then are caused by receptions after jumping and changes of direction own of this sport. Here, we show the importance of a proprioceptive program to avoid injuries in football that shows its practical applicability in daily training. Our approach is based on important scientific research of different collective sports. In addition, we organize the training following the fundamental principles of training. In this sense, specific materials are used (unstable platforms, fitballs, etc.) and exercise with real applicability to the game that will provide the player with optimal a rapid response to a possible injury. Our work attempts to demonstrate that intervention carried out would have a preventive effect on the frequency of football injuries, providing effective responses and improvements in strength, coordination, balance, reaction time to specific sports situations. Lastly, we also want to highlight the importance of the multidisciplinary work of doctors, trainers, physical trainers, adapters and physiotherapist ass an essential factor to minimize the number of injuries.